Accessibility as far as the eye can see: an accessible film festival - Martins, Cláudia (2020)
Currently, we can no longer speak of monolingual societies but rather of a linguistic heterogeneity that cuts across every sector of society. In line with this tendency, numerous international and national laws have been signed; however, few have come into actual effect, as is the case of Portugal, where we could mention not only the ratification of the Convention of the Rights of Persons with Disabilities (only in 2009), but also the “Lei anti-discriminatória em razão da deficiência” [Anti-discrimination law for reasons of disability] in 2006, as well as the national constitution in its article number 71 (1976, 1997). If, on the one hand, we all agree on the need for linguistic mediation for language minorities, in this particular case, people with sensory impairments, on the other, only scattered measures, initiatives or events can be pinpointed. In this presentation, we seek to report on the I Accessible Film Festival that was held in Bragança, northeast of Portugal, in May 2019, for the first time in our country. As such, we will attempt to approach the festivals that deal with the topic of accessibility for people with sensory disabilities. Accessible festivals showcase not only films made by people with disabilities, but also festivals that include such modalities as audiodescription (AD), subtitling for the deaf and hard-of-hearing (SDH) and/or sign language interpreting (SLI). Historically speaking, the first film festival to make use of AD is said to be Cannes Festival in 1989. Others followed suit, such as the Berlin International Film Festival or the Film Fest Gent. It has been a slow but steady progress to reach the stage where disability became the focus of some festivals: these are the cases of the Filmfest München, the Brazilian International Film Festival on Disability Assim Vivemos (Costa, 2010), Superfest International Disability Film Festival (San Francisco) or the International Film Festival on Disability (France), among others. Therefore, our aim with this paper is two-fold: we seek to review the major national and international film festivals dedicated to disability and/or accessibility so as to understand the array of choices they offer, and report on our accessible cinema festival, a joint organization of the IPB and the Avanca Film Club, on its way to its second edition.